GENDER DIFFERENCES OF STENT IMPLANTATION COMPLICATIONS. ASSESSMENT OF ACUTE CORONARY SYNDROME WITH ST ELEVATION - Gujejiani, Lali; Sharashidze, Nino; Mamatsashvili, Merab; Tvalchrelidze, Shalva; Taboridze, Iamze; Aladashvili, Lali; Naphetvaridze, Rusudan (European Scientific Journal, ESJ, 2014)
The aim of study is the assessment of Gender differences of stent implantation procedure complications with ST elevation patients. Materials and methods: 110 patients with ST elevation of ltd ADAPTI angiocardiology hospital (2009-2010) were enrolled in the study. The stent implantations were performed. Among them were: 58 men and 52 women. The average age of men: 66.44±4.78, women: 66.65±5.68. In order to reveal the complications predictors, two groups were compared: the patients with complications and the patients without complications. The alternative test was also performed in order to assess the complications risk factors according to gender. Quantity data were compared according to - t (student) criteria and qualitative data – according to - F (fisher) criteria. Clinical data were processed with statistical programs package SPSS 16.0. Results: There are essentially high indexes of the following risk factors in women: Hypertension – 53% and 77%, p=0.0099; Dislipidemia – 14% and 50%; p=0.0000 and hypotension before stent implantation – 16% and 38%; p=0.0240. EF is significantly higher in men then in women (accordingly 46.83±9.435 and 41.04±10.288; p=0.00280, but troponin I is less in men: 0.29±0.201 and 0.37±0.179, p=0.0272.) Stent implantation procedure complications were presented in men 63.64% and in women 61.54 %, also the frequency of procedure dissection was higher in men. (Men- 17% and women 4%, p= 0.0244.) . The data of LDA were higher in women group with complications – 58 % and 19% (p=0.0045), the damage of multiple vessels – 55% and 24 % (p=0.0262), hypertension – 87% and 62% (p= 0.0348), Diabetes Melitus – 55% and 24% (p= 5.25). The complication predictors were not revealed in men.